2004
DOI: 10.1111/j.1526-4610.2004.04027.x
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Tolerability of Oral Zolmitriptan in Menstrually Associated Migraine: A Randomized, Prospective, Parallel‐Group, Double‐blind, Placebo‐Controlled Study

Abstract: Oral zolmitriptan exhibits efficacy and good tolerability in the treatment of menstrually associated migraine. Improvement over placebo was observed as early as 30 minutes following treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
63
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(64 citation statements)
references
References 17 publications
1
63
0
Order By: Relevance
“…At 2-hours, headaches were still responsive in 48% of zolmitriptan treated attacks as compared with 27% with placebo. 86 Although there are no direct comparator studies between any triptans for short-term prophylaxis of MRM, frovatriptan, sumatriptan, naratriptan and zolmitriptan have shown to be effective short-term prophylactic agents for MRM. [87][88][89][90] Tuchman et al evaluated the effi cacy of zolmitriptan for the shortterm prophylaxis of MRM.…”
Section: Effi Cacy In Menstrually-related Migrainementioning
confidence: 99%
“…At 2-hours, headaches were still responsive in 48% of zolmitriptan treated attacks as compared with 27% with placebo. 86 Although there are no direct comparator studies between any triptans for short-term prophylaxis of MRM, frovatriptan, sumatriptan, naratriptan and zolmitriptan have shown to be effective short-term prophylactic agents for MRM. [87][88][89][90] Tuchman et al evaluated the effi cacy of zolmitriptan for the shortterm prophylaxis of MRM.…”
Section: Effi Cacy In Menstrually-related Migrainementioning
confidence: 99%
“…Several triptans have been assessed for efficacy in the short-term prevention of migraine associated with menses [Newman et al, 2001;Silberstein et al, 2004b, Loder et al, 2004. Naratriptan and frovatriptan have been reported to be effective in short-term prophylaxis of menstrually associated migraine.…”
Section: Triptansmentioning
confidence: 99%
“…Zolmitriptan, in doses of 1.25À5 mg, was investigated in a placebo-controlled study of a single menstrual migraine attack. 50 At a dose of 2.5 mg, oral naratriptan was evaluated in a randomized double-blind placebo-controlled study and it was found, in subjects receiving active drug, that a pain-free response was maintained from 4 to 24 hours. 51 Frovatriptan has been studied in several studies, and has demonstrated consistent results.…”
Section: Treatmentmentioning
confidence: 99%